Natural Bioactives Targeting the GLP-1 Pathway: A Promising Approach for Diabetes Management - Kolhe, Rohini Chandrakant; Chaudhari, Priyanka Sudhakar; Khaire, Manisha Pradeep; Ghadage, Priyanka Kantaram; More, Archana Sopan (Pharmacognosy Reviews)
Diabetes, a disorder that is becoming more and more common in the world; however, it affects over 400 million people worldwide. Despite considerable growth in diabetes management, most patients often suffer from a significant number of adverse effects and complications of current treatment plans. Therefore, the best action would be collaborating differently for exploring new therapeutic possibilities. The Glucagon-Like Peptide-1 (GLP-] agonist has a huge role in glucose homeostasis which control insulin secretion and inhibits the release of glucagon with prompts slow gastric emptying. This review covers natural products that modulate the GLP-1 path, presenting a few hope-giving possibilities in diabetes care. Natural products related to plants have shown promising effects on the GLP-1 agonist pathway. Compounds like berberine, from a variety of plants, have been observed to increase GLP-1 secretion with an increase in insulin sensitivity. Ginsenosides from ginseng and curcumin from turmeric have similar activities. This article reviews the mechanisms by which these natural products alter the GLP-1 pathway. It also surveys some expected benefits of the used compounds in diabetic therapy, such as drastically reduced side effects and extra health benefits of anti-inflammatory and antioxidant properties. Henceforth, natural modulators of the GLP-1 pathway seem to aim an excellent and promising new direction for the care of diabetes.
Keywords: GLP-1 Pathway; Diabetes Mellitus; Natural Products; Phytochemicals; Insulin Secretion